PENGARUH E-TRUST, E-SERVICE QUALITY DAN E-SATISFACTION TERHADAP E-LOYALITY PENGGUNA BSI MOBILE PADA PENGADILAN AGAMA PASCA SERANGAN CYBERRASOMWARE - Muhajir, Ammar; Pahlevi, Rizal (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2024)
Amid current technological developments, many innovations are making life more accessible for people to interact, get information, and transact. This is especially evident in the Banking sector, which is experiencing digitalization with BSI mobile services. This study aims to determine how E-Trust, E-Service Quality, and E-Satisfaction affect the E-Loyalty of Bank Syariah Indonesia Mobile Banking users after cybercrime attacks (religious court survey employees). This research utilizes a quantitative approach by relying on numerical data. This research uses data sources in the form of numbers. The process used to collect data is distributing questionnaires to 50 religious court employees who are BSI customers. The method used in sampling is purposive sampling. The data analysis technique used in this study uses multiple linear regression techniques to test the effect of the independent variable on the dependent variable, both partial and simultaneous effects. The overall result of this study is a statement that shows that E-Trust and E-Service Quality have a positive and significant influence on E-Loyalty. In contrast, e-satisfaction does not have an impact and is not substantial in e-loyalty.